Photoinduced and Thermal Single‐Electron Transfer to Generate Radicals from Frustrated Lewis Pairs - Holtrop, Flip; Jupp, Andrew R.; Leest, Nicolaas P.; Paradiz Dominguez, Maximilian; Williams, René M.; Brouwer, Albert M.; Bruin, Bas; Ehlers, Andreas W.; Slootweg, J. Chris (Chemistry : a European journal, 2020)
Archetypal phosphine/borane frustrated Lewis pairs (FLPs) are famed for their ability to activate small molecules. The mechanism is generally believed to involve two‐electron processes. However, the detection of radical intermediates indicates that single‐electron transfer (SET) generating frustrated radical pairs could also play an important role. These highly reactive radical species typically have significantly higher energy than the FLP, which prompted this investigation into their formation. Herein, we provide evidence that the classical phosphine/borane combinations PMes3/B(C6F5)3 and PtBu3/B(C6F5)3 both form an electron donor–acceptor (charge‐transfer) complex that undergoes visible‐light‐induced SET to form the corresponding highly reactive radical‐ion pairs. Subsequently, we show that by tuning the properties of the Lewis acid/base pair, the energy required for SET can be reduced to become thermally accessible. Exciting FLPs! The radical‐ion pairs of the archetypal frustrated Lewis pair (FLP) systems PMes3/B(C6F5)3 and PtBu3/B(C6F5)3 can be accessed by visible‐light‐induced single‐electron transfer. Varying the FLP system shows this process is general for a range of donor–acceptor combinations and can be tuned to proceed thermally.